THE PROCESS OF ESTABLISHING THE ADMINISTRATIVE SYSTEM FROM NGANG PASS TO THE SOUTHWESTERN REGION (XI - XVII CENTURY) - Bùi Văn Hùng (Tạp chí Khoa học Đại học Đà Lạt)
From the eleventh to the seventeenth century, Vietnamese feudal dynasties consistently strengthened national independence. In that process, the formation of territorial boundaries is a particularly important issue, especially in the southern area of the country. The establishment of administrative units from Ngang Pass (Horizontal Pass) to the southernmost point of the country is not only a matter of territorial claims, but also a matter of great significance for the development of the nation. The article deals with the establishment of sovereignty, production organization, and security - cultural - social stability of the dynasties. The Lý and Trần dynasties established administrative units in northern Hải Vân Pass, the Hồ and Later Lê dynasties established administrative units north of Cù Mông Pass, and the Nguyen Lords asserted territorial claims from Cù Mông Pass to Hà Tiên. The research results aim to provide information and historical materials for lecturers and students of social sciences and humanities disciplines of Dalat University, as well as those who are interested in this topic.